Analisis Pengaruh User Experience Portal Berita Terhadap Citra Merek (Studi Pada Portal Berita XYZ) - Roni Yulistyo Saputra; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
User experience is the experience acquired in its interactions with users website or application .User experience when using perceived users website or application on users more telling than in conventional uses the media .While brand image is perception , the assessment of , confidence the customers to the brand .This research has objective to known the impact user experience on brand image , then know get any variable variable that affects the impact of the location and recommend ways to improve a positive image of trademark through user experience. A trademark that used are website of news portal in Indonesia. News portal has had a good ranking on alexa.com and similar web. in alexa.com and similar web based on a visit daily and pageview .Visits daily and pageviews can be influenced by the user experience To research it uses 6 from 7 of variable presented by de angeli for measuring. user experience .Research did not use all the variables user experience of the theory suggested de angeli. One variable service quality is not used because the variable is measuring the quality of services like e-commerce while it was not provided by the website or. news portalAs for measuring brand image using a theory of. Keller Data obtained on this research using methods kuisioner.We do. dependent variable for independent testing Based on the data generated from multiple linear regression testing by, user experience having influence against tribunnews.com brand image.